Search Intermediary Elicitations During Mediated Online Searching - Spink, Amanda; Goodrum, Abby; Robins, David (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
What elicitations or requests for information do human search intermediaries make to patrons search with information requests that require an online search? What intermediary elicitations occur before and during an online search? Why do human search intermediaries make elicitations? This study reported in this paper investigated search intermediary elicitations during mediated online searching. A study of 40 online reference interviews involving 1557 search intermediary elicitations, found 15 different types of search intermediary elicitations to patrons. The elicitation purposes included search terms and strategies, database selection, relevance of retrieved items, and patrons' knowledge and previous information-seeking. Analysis of the patterns in the types and sequencing of elicitations showed significant strings of multiple elicitations regarding search terms and strategies, and relevance judgments. This paper discusses the implications of the findings for training search intermediaries and the design of interfaces eliciting information from end-users.